2005
DOI: 10.1063/1.1851951
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of face-centered-cubic and hexagonal-close-packed Ni nanoparticles through polyol process

Abstract: The Ni nanoparticles with fcc or hcp phases have been synthesized in tetraethylene glycol by using the modified polyol process. The crystal structure has been controlled by changing the polyol/Ni mole ratio and the reaction temperature. The saturation magnetization of the as-prepared particles depends on the relative volume fraction of the hcp phase. The x-ray diffraction and extended x-ray absorption fine structure studies suggest the formation of pure fcc and hcp Ni phases. The hcp Ni particles show nonmagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 7 publications
5
65
1
3
Order By: Relevance
“…Recently, the synthesis and characterization of nanocrystalline hcp Ni have been attracting widespread attention because of their unique magnetic properties and improved performances by their particle sizes, crystal structures and inter-particle interaction [14][15][16]. Nanosized Ni can be fabricated by a variety of physical and chemical methods including pyrolysis, sputtering, reversed micelles, aqueous and nonaqueous chemical reduction, sonochemical deposition, and polyol [17][18][19][20]. Mi et al [14], Chinnasamy et al [17], and Jeon et al [18] successfully synthesized pure fcc Ni nanoparticles, hcp Ni nanoparticles and a mixture of fcc and hcp Ni nanoparticles in different organic solvents using a chemical reduction method under free-standing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the synthesis and characterization of nanocrystalline hcp Ni have been attracting widespread attention because of their unique magnetic properties and improved performances by their particle sizes, crystal structures and inter-particle interaction [14][15][16]. Nanosized Ni can be fabricated by a variety of physical and chemical methods including pyrolysis, sputtering, reversed micelles, aqueous and nonaqueous chemical reduction, sonochemical deposition, and polyol [17][18][19][20]. Mi et al [14], Chinnasamy et al [17], and Jeon et al [18] successfully synthesized pure fcc Ni nanoparticles, hcp Ni nanoparticles and a mixture of fcc and hcp Ni nanoparticles in different organic solvents using a chemical reduction method under free-standing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that the hexagonal phase synthesized in the polyol solution changes to the fcc phase by annealing. 7) Hence a significant change of magnetization due to the crystallographic transition is expected by annealing for the specimen synthesized with PVP. To appear the crystallographic transition temperature, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the hexagonal phase synthesized in the polyol solution has been characterized as non-magnetic because the saturation magnetization becomes lower as the volume fraction of the hexagonal phase increases with decreasing Ni salt concentration. 7) Since the saturation magnetization for the fcc phase is much larger than that for the hexagonal phase, the magnetization measurement is meaningful to examine the influence of PVP on the volume fraction of the fcc phase in more detail. for the specimen synthesized with 15 g/L PVP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations